Using the Minor Agreements - McLoughlin, Michael (Ephemerides theologicae Lovanienses, 2018)
According to the Two Source theory (2ST) Matthew and Luke derived their triple tradition material by copying Mark. But occasionally the others agree against Mark. These agreements are slight, but they could suggest that Mark was not the only source. Authors who contest the 2ST frequently cite these minor agreements as evidence against that theory. An attempt is made here to identify the most weighty cases. Forty were found. These are explained as independent reactions by Matthew and Luke to the Markan text, so that the 2ST is safe from objection. In addition, rival source theories are positively discouraged.